The Preparation of Black Goji Berry Enzyme and Its Therapeutic Effect on Alcoholic Liver Injury in Mice - Keshan Wang; Zhishan Zhang; Wenge Xu; Shuyuan Yang; Jing Zhao; Zeyu Wu; Wencheng Zhang (Foods)
This study aimed to prepare a black goji berry enzyme (BGBE) using high acyl gellan gum as a substitute for aqueous slurry, followed by fermentation with Saccharomyces cerevisiae (SC) for 48 h, pasteurization, and subsequent fermentation with Lactobacillus plantarum (SC) for 48 h to obtain the optimal BGBE sample. The anthocyanin content and in vitro antioxidant activity were significantly enhanced. The primary objective of this study was to evaluate the potential therapeutic effect of BGBE on alcoholic liver injury (ALD) in mice. An animal model of alcoholic liver injury was established, and the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), triglycerides (TG), total cholesterol (TC), malondialdehyde (MDA), superoxide dismutase (SOD), alcohol dehydrogenase (ADH), and aldehyde dehydrogenase (ALDH) in the serum and liver were analyzed. Furthermore, histopathological examination was performed using hematoxylin–eosin staining. The results indicated that BGBE significantly improved the liver histopathological condition in mice, markedly reducing the serum levels of ALT, AST, TG, TC, and the hepatic MDA levels (p < 0.05), while significantly increasing the levels of SOD, ADH, and ALDH (p < 0.05). The therapeutic effect of BGBE on alcoholic liver injury appears to be associated with its antioxidant properties.